Respuesta :

Answer: The roots of question 1) -6 , 2 (Brown)

2) -7, 1  (light brown)

3) 3, -1  (yellow)

4) [tex]\frac{2\pm \sqrt{19} }{3}[/tex] (orange)

5)[tex]3\pm \sqrt{15}[/tex] (Red)

6)[tex]\frac{-5\pm3\sqrt{5} }{2}[/tex]  (Brown)

Step-by-step explanation:

Since, First quadratic equation is, [tex]x^2+4x-12=0[/tex]

⇒[tex]x^2+6x-2x-12=0[/tex]

⇒[tex]x(x+6)-2(x+6)=0[/tex]⇒[tex](x-2)(x+6)=0[/tex]

Therefore, root of  [tex]x^2+4x-12=0[/tex] are x = 2, -6

Now,Second quadratic equation is, [tex]2x^2+12x-14=0[/tex]

⇒[tex]2x^2+14x-2x-14=0[/tex]

⇒[tex]2x(x+7)-2(x+7)=0[/tex]⇒[tex](2x-2)(x+7)=0[/tex]

Therefore, root of  [tex]2x^2+12x-14=0[/tex] are x = 1, -7

Third quadratic equation is, [tex]x^2-2x-3=0[/tex]

⇒[tex]x^2-3x+x-3=0[/tex]

⇒[tex]x(x-3)+1(x-3)=0[/tex]⇒[tex](x-3)(x+1)=0[/tex]

Therefore, root of  [tex]2x^2+12x-14=0[/tex] are x = -1, 3

fourth quadratic equation is,  [tex]3x^2-4x-5=0[/tex]

By applying quadratic formula, roots of the equation [tex]3x^2-4x-5=0[/tex]are

[tex]x=\frac{2\pm 19}{3}[/tex]     ([tex]x=\frac{-b\pm\sqrt{b^2-4ac}}{2a }[/tex])

Similarly, By the quadratic formula,

The roots of [tex]x^2-6x+4=0[/tex] are [tex]3\pm \sqrt{15}[/tex]

And, roots of [tex]3x^2-4x-5=0[/tex] are [tex]\frac{-5\pm3\sqrt{5} }{2}[/tex]